Reading Culture from the Psychological and Educational Perspectives - Pečjak, Sonja (Revija za elementarno izobraževanje, 2021)
The article discusses reading culture and reading as a value in Slovenia, withtheoretical considerations supported by empirical results of foreign anddomestic psychological and educational studies on reading culture. In thispaper we try to answer the questions of what reading culture is and what itselements are, when reading can become a value and what the obstacles are inthe development of reading culture from the psychological perspective. Weanswer these questions from the perspective of the family and schoolenvironment and suggest some ways of dealing with these obstacles, especiallyfrom the perspective of the role of the family and the school or teachers, aspointed out by the National Strategy for the Development of ReadingLiteracy.
Keywords: reading culture, development of reading culture, family, school – teachers and teacher education